Analysis of the Impact of Production Instability, Coal Benchmark Price, Labor Productivity, and Exchange Rate on the Value of Coal Exports to India - Dzalika Friska Soraya Pelleh; Raden Parianom (Journal Of Social Science (JoSS), 2026)
This research was conducted to analyze the influence of Indonesian coal production, the Indonesian coal reference price, Indonesian labor productivity, and the currency exchange rate on the value of coal exports to India over the period 1994–2024. Secondary annual data were obtained from Badan Pusat Statistik (BPS, Central Bureau of Statistics), the Ministry of Energy and Mineral Resources, and Refinitiv. The study employed the Error Correction Model (ECM) method to examine the influence of each variable in both the short term and the long term. The research findings indicate that, in the short term, the variables of Indonesian coal production, Indonesian labor productivity, and the currency exchange rate do not have a significant effect on the value of coal exports to India. However, the Indonesian coal reference price has a significant effect on the value of coal exports to India. In the long term, the variables of the Indonesian coal reference price and Indonesian labor productivity significantly influence the value of coal exports to India, while the variables of Indonesian coal production and the currency exchange rate do not have a significant relationship with the value of coal exports to India.